Theoretic and experimental study of photoprocesses in substituted 4-dicyanomethylene-4H-pyrans - Pomogaev, Vladimir A.; Svetlichnyi, Valerii A.; Pomogaeva, A. V.; Svetlichnaya, N. N.; Kopylova, Tatyana N. (High energy chemistry)
The photoprocesses in substituted 4-dicyanomethylene-4H-pyran (DCM) derivatives were studied theoretically and experimentally. The experimental spectral and luminescent parameters of the molecules under study are in good agreement with the results of quantum-chemical calculations. Trends changes in the spectral and luminescent properties depending on the molecular structure were established. The appearance of the S2 level near the S1 level in the scheme of the energy states of symmetrically substituted DCM (bis-DCM) causes changes in photophysical processes and a drop in the ﬂuorescence quantum yield.